Point Of Sales (POS) Application On Clients of PT. Esensi Solusi Buana - Ria Wulandari; Siti Maesaroh; Erwansyah Erwansyah (Universitas Raharja, 2021)
Point of Sales application is a system used for transaction data into the database both by input and output, so that there are no errors in input, output data, and report generation based on the corresponding data, thus it can produce accurate output data. PT Esensi Solusi Buana is a company engaged in the field of technology and information. Based on surveys and interviews with clients of PT Esensi Solusi Buana, it is obtained the information about the operating system that is still manual and less than optimal.This causes frequent errors in recording sales transaction data, archiving that still uses the traditional system, as well as access to obtain information about the transaction history that requires a lot of time. Therefore, the system to be made is an improvement of the system that was previously made for the clients of PT Esensi Solusi Buana. It is expected that with this system, it can minimize errors that may occur. This system is also expected to be able to improve the process of input, output, and report generation, which in turn can help data collection of sales transactions on the clients of PT Esensi Solusi Buana